(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines the role of color components in word formation within the English language. It explores how colors are used to create descriptive adjectives, nouns, compound words, and idiomatic expressions, drawing on cultural, psychological, and linguistic aspects. The study reveals that color terms not only serve as descriptors but also carry metaphorical meanings that reflect emotions, social identities, and cultural values. The impact of color-based word formation on English vocabulary and communication is explored in-depth.